Evaluation and proposal for a new PMC Pea Harvester Support System - Coalter, Neil (Cranfield University, 2008)
PMC Harvesters Ltd is an OEM (Original Equipment Manufacturer) for the pea and bean market. Their primary product line is a self propelled harvester known as the 979 CT harvester. The 979 CT is of considerable proportions being 4m x 4m x 12m in overall dimensions, six wheel drive and weighs 29,620 kg GVW (Gross Vehicle Weight) when fully laden. The aim of this work was to identify and outline possible solutions for the support system (tyre or track and undercarriage), quantify the performance of each system, produce a design and evaluation method to determine an optimal structural specification and to produce a design recommendation for the application. Analysis of the current 979 CT harvester wheel configuration highlighted many constraining factors in tyre choice. The most pertinent of these was that the wheels have a very limited operating space and following a study of the possible tyre options it became apparent only two manufactures, Michelin and Trelleborg, could provide tyres which met the vehicle parameters. An experiment was conducted to evaluate the performance of the three chosen tyre options. From the findings of these tests it was clear that the optimal tyre for the PMC configuration was the Trelleborg Twin Radial tyre, operating at minimum road inflation pressure (1.6 bar) as designated by Trelleborg. When operating the harvester in its normal working environment the tyre pressure should be set at minimum road inflation for in-field conditions with a DBD (Dry Bulk Density) of > 1.3 g/cm3, as excess damage caused by operating above minimum field operating pressure is superficial. The use of low compaction equipment such as CTIS (Central Tyre Inflation System) or tracks would not be beneficial to the PMC application. The track tested created a hardened track pan, thus requiring more effort to rectify post harvest. A CTIS increases the consumption of diesel and offered no reduction in soil compaction below plough depth as shown by the findings from operating the optimal tyre at minimum field inflation pressure (1.2 bar). The primary objective of this project was to offer solutions to reduce the effects of the PMC harvester’s weight on its operating medium. The first natural step was to assess the vehicles main structure in order to improve its performance to weight ratio. The initial phase of this process was to validate the modelling and analyses techniques used to assess the structure. This was done within a controlled test environment at CU@S and from this work a factor of safety of 10% was designated to be applied to all analysis in order to authenticate results and generate a “worst case” answer. Revisions of the main chassis, main pivot and rear axle assemblies were created and analysed. Test metrics were defined which represented operating patterns of the harvester. The findings from these tests saw a 22.6% weight reduction, 43.1% increase in life expectancy and 10.2% reduction in peak stress in the main chassis and main pivot. Unlike the other two key assemblies, the rear axle was deemed fit for purpose and would not benefit from any further design changes.